Analysis of Organizational Culture, Human Resource Quality, and Work Discipline on the Performance of Educational Support - Dadan Hendayana (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
Global competition in higher education demands optimal performance from all elements, including educational support staff as the operational backbone. This study aims to analyze the influence of organizational culture, human resource (HR) quality, and work discipline on the performance of educational support staff at Langlangbuana University (a private higher education institution in West Java). A quantitative approach with a survey method was used on 92 respondents (from a population of 118) selected through stratified random sampling. Data analysis included descriptive statistics, multiple linear regression, and path analysis. The simultaneous test results show that the three independent variables have a significant effect on performance. Partially, HR quality has the most dominant influence, followed by organizational culture. The novelty of this study is that work discipline does not have a significant direct effect on performance, indicating that in the context of a private higher education institution, work discipline functions as a supporting variable whose influence is mediated by competence and culture. Managerial implications: universities should prioritize sustainable competency development programs, strengthen a collaborative-innovative culture, and revitalize the work discipline approach from a rigid model to an integrated coaching model linked with the performance appraisal system.